PREGNANT WOMEN WITH PYELONEPHRITIS (American Journal of Interdisciplinary Research and Development, 2023)
The article presents cases of cardiovascular changes against the background of pyelonephritis in pregnant women in the second and third trimesters of pregnancy. The course of pregnancy, the manifestation of comorbidity, the factors that contributed to the development of these phenomena were studied. The work was carried out at the SamSMU Clinic No. 1 for 2021-2022. It was found that comorbidity in pregnant women violates the physiological course of pregnancy, affecting both the mother and the child. With pyelonephritis in pregnant women, complications from the cardiovascular system are observed, which aggravates pregnancy and childbirth